2016
DOI: 10.5430/cns.v4n2p48
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the learning style and study habit of students in the faculty of nursing of Al Jabal Al Gharbi University, Gharyan, Libya

Abstract: Through learning, everyone becomes educated but learners should have a style to learn and possess a habit that match how they study. These two variables are vital as guide for educators or mentors to come up with such methodology or strategy in promoting quality and effective teaching-learning environment. With this, it is the purpose of this study to investigate the learning style and study habit of students in the Faculty of Nursing, Al Jabal Al Gharbi University, Gharyan, Libya according to their gender, ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A related challenge for student nurses is professional advancement and compensation after graduation. Students are less likely to finish their baccalaureate nursing studies if they maintain a bleak outlook on their future career prospects (Kiblasan et al., 2016). Educational institutions in Libya reported having limited connections to hospitals and other potential employers within the health care job market.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A related challenge for student nurses is professional advancement and compensation after graduation. Students are less likely to finish their baccalaureate nursing studies if they maintain a bleak outlook on their future career prospects (Kiblasan et al., 2016). Educational institutions in Libya reported having limited connections to hospitals and other potential employers within the health care job market.…”
Section: Resultsmentioning
confidence: 99%
“…Reinforcing the messages about the importance of educational preparation for nurses, hospitals, and health systems should differentiate salaries and roles based on academic preparation. Currently, there is little incentive to devote additional resources to pursuing a baccalaureate when the wages are roughly equivalent between diploma graduates and baccalaureate‐prepared nurses (Kiblasan et al., 2016). A National Nursing Council could influence the Department of Health to differentiate pay scales for nurses based on education and eventually certify nurses with a universal test prior to practice.…”
Section: Resultsmentioning
confidence: 99%
“…The employees in tourism industry should fulfill some requirements and skills to be a professional hotelier. To be a professional hotelier, students should have good study habits in time budgeting, taking note ability, reading ability, memorizing ability, good health, studying based on the learning styles and learning motivation (Khursid, 2012;Kiblasan, 2016;Magulod, 2019;Sabbah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are some factors that impact the study habits of the students. Kiblasan (2016); Mohit, (2019) found that gender, economic status, year level and learning styles have significant impact in study habits of the students. Learning styles are the various ways of learning to absorb the material efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Through education, learners can make a significant advancement, yet it is vital for educators to ensure teaching effectiveness to promote a high-quality teaching-learning environment. All tertiary or higher education institutions and technical colleges aim to improve their students' learning capability and then guide them in their matched study habits to promote learning [18,20,24,26,34,35].…”
mentioning
confidence: 99%